Designing a Web-Based Cake Ordering System to Increase Accessibility and Efficiency Using the Extreme Programming Method at Dapur Bolu Ibu Kokom - Grasela Asta Miranda; Tedjo Darmanto; Moch. Irwan Hermanto (Universitas Suryakancana Cianjur, 2025)
Digital transformation is driving the development of the culinary industry, including the cake and bread business. However, Dapur Bolu Ibu Kokom still uses a conventional ordering system that often leads to errors in recording orders and inefficiency of available stock. This research aims to design a web-based sponge cake ordering system to improve operational efficiency and customer satisfaction. Extreme Programming (XP) method is used to ensure the flexibility and responsiveness of the system by using javascript programming language and Unified Modeling Language system architecture design and blacbox testing system testing. The system features registration, login, ordering, stock checking, and delivery status. The results show that this system improves recording accuracy, speeds up ordering, and provides transparent stock and delivery information. Thus, the implementation of this system supports the digitalization of the culinary business and improves operational efficiency.